Investigating Electrode Flooding in a Flowing Electrolyte, Gas‐Fed Carbon Dioxide Electrolyzer. Issue 2 (17th December 2019) - Leonard, McLain E.; Clarke, Lauren E.; Forner‐Cuenca, Antoni; Brown, Steven M.; Brushett, Fikile R.
Abstract: Managing the gas–liquid interface within gas‐diffusion electrodes (GDEs) is key to maintaining high product selectivities in carbon dioxide electroreduction. By screening silver‐catalyzed GDEs over a range of applied current densities, an inverse correlation was observed between carbon monoxide selectivity and the electrochemical double‐layer capacitance, a proxy for wetted electrode area. Plotting current‐dependent performance as a function of cumulative charge led to data collapse onto a single sigmoidal curve indicating that the passage of faradaic current accelerates flooding. It was hypothesized that high cathode alkalinity, driven by both initial electrolyte conditions and cathode half‐reactions, promotes carbonate formation and precipitation which, in turn, facilitates electrolyte permeation. This mechanism was reinforced by the observations that post‐test GDEs retain less hydrophobicity than pristine materials and that water‐rinsing and drying electrodes temporarily recovers peak selectivity. This knowledge offers an opportunity to design electrodes with greater carbonation tolerance to improve device longevity. Abstract : A matter of time : Gas‐diffusion electrodes (GDEs) for carbon dioxide electroreduction are screened over a range of applied current densities, and an inverse correlation is observed between carbon monoxide selectivity and the electrochemical double‐layer capacitance, a proxy for wetted electrode area. This knowledge offers an opportunity to design electrodes with greater carbonation tolerance to improve device longevity.